Combustion characteristics; manufactured carbon and graphite products; catalysts - Materials, American Society for Testing & ([S.l.] : ASTM, 2009)
This volume covers test methods that are used to determine the knocking or detonation characteristics of motor and aviation fuels and the ignition characteristics of diesel fuels.